2016
DOI: 10.1186/s12888-016-0890-x
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of conversion disorder: overview and meta-analysis of neuroimaging studies on motor conversion disorder

Abstract: BackgroundConversion Disorders (CD) are prevalent functional disorders. Although the pathogenesis is still not completely understood, an interaction of genetic, neurobiological, and psychosocial factors is quite likely. The aim of this study is to provide a systematic overview on imaging studies on CDs and investigate neuronal areas involved in Motor Conversion Disorders (MCD).MethodsA systematic literature search was conducted on CD. Subsequently a meta-analysis of functional neuroimaging studies on MCD was i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 107 publications
3
32
0
3
Order By: Relevance
“…In line with previous studies [1,2], we postulate that functional stroke mimics are specifically determined by a dysfunction in high-order associative areas along with the subsequent perturbation of motor/premotor areas.…”
Section: Figsupporting
confidence: 88%
See 3 more Smart Citations
“…In line with previous studies [1,2], we postulate that functional stroke mimics are specifically determined by a dysfunction in high-order associative areas along with the subsequent perturbation of motor/premotor areas.…”
Section: Figsupporting
confidence: 88%
“…Functional neurological disorders (FND) are characterized by neurological symptoms that cannot be attributed to an organic brain aetiology, but rather that can be associated with emotional stressors acting as precipitating factors [1,2]. Different terms have been used, including conversion disorder and psychogenic or dissociative neurological symptoms [1].…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional neuroimaging studies have demonstrated a failure to activate contralateral motor (Marshall et al, 1997;Stone et al, 2007) and premotor cortex during action execution, action selection (Voon et al, 2011), movement observation (Burgmer et al, 2006) and during recall of clinically repressed events (Kanaan et al, 2007) in affected patients. In addition, prefrontal areas, insula, amygdala and anterior cingulate cortex have been implicated in motor conversion disorder (Boeckle et al, 2016).…”
Section: Introductionmentioning
confidence: 99%